The Resilience of Social Service Providers and Families of Children With Autism or Development Delays During the COVID-19 Pandemic—A Community Case Study in Hong Kong - Wong, Paul Waiching; Lam, Yanyin; Lau, Janet Siuping; Fok, Hungkit (Frontiers in Psychiatry, 2021)
Background Hong Kong is one of the earliest cities to have hampered by the COVID-19. When preventive public health measures are enforced, specific groups, who have already been facing inequality before the outbreak, are likely to become more overlooked and vulnerable. Aim This community case study aims to describe the additional needs of families of children with autism spectrum disorder (ASD) and other developmental issues, as well as document difficulties and challenges social service professionals encountered when delivering service and their solutions towards these challenges. Methods A focus group with ten professionals providing the Caregiver Skills Training Programme was conducted. Results Poor families of vulnerable children were found to be challenged, more than average, in finding daily necessities during the initial stage of the outbreak. Most vulnerable children displayed additional problematic behaviors and emotional problems during the quarantine. The social service professionals addressed the family needs by providing tangible resources and offering online training, workshops, and programs to match their needs. Several important lessons were learned. First, technology-know-how on conducting online training, workshop, and program could be a challenge to some social service professionals and the parents. Second, the professionals reported that they made huge efforts to produce guidelines in protecting services users’ privacy, to equip themselves with necessary skills in executing privacy-protection measures, and to keep exploring for safer alternatives. Third, providing services in online mode represented a different interaction pattern between social service professionals and service users, especially in recruitment processes and group dynamics. Conclusion In comparison with other cities, Hong Kong has responded to the COVID-19 efficiently and effectively based on the citizen’s strict adherence to behavioral advice and the efficient and innovative altruistic efforts from the multi-sectors in the community.